Human Papillomavirus Type Distribution in Cervical Intraepithelial Neoplasia Grade 2/3 and Cervical Cancer in Portugal: A CLEOPATRE II Study - Pista, A (2013)
OBJECTIVE: Cervical cancer is the third most frequent cancer in women, worldwide and etiologically associated with infection by human papillomavirus (HPV). Following the results of the first epidemiologic population-based CLEOPATRE study in Portugal, it was important to understand the HPV type-specific distribution in women with cervical intraepithelial neoplasia (CIN) grades 2 and 3 and invasive cervical cancer (ICC). METHODS: This was an observational, multicenter, cross-sectional study with retrospective data collection. Between January 2008 and May 2009, paraffin-embedded samples of histologically confirmed cases of CIN2, CIN3, and ICC were collected from the 5 regional health administrations in mainland Portugal. Eligible samples were sent to 2 central laboratories for histological reassessment and HPV genotyping. Prevalence estimates were calculated together with 95% confidence intervals. RESULTS: A total of 582 samples, 177 cases of CIN2, 341 of CIN3, and 64 of ICC, were included. The mean age of participants was 41.8 years (range, 20-88 years). The overall HPV prevalence was 97.9% with a higher prevalence of high-risk genotypes, particularly HPV 16. Multiple infections were observed in 11.2% of the cases. Human papillomavirus prevalence was 95.5% in CIN2, 99.4% in CIN3, and 96.9% in ICC. The 8 more frequent genotypes in order of decreasing frequency were HPV 16, 31, 58, 33, 51, 52, 18, and 35 in CIN2 and HPV 16, 31, 33, 58, 52, 35, 18, and 51 in CIN3. In ICC cases, the 12 detected HPV genotypes were HPV 16, 18, 31, 33, 45, 51, 52, 53, 56, 58, 59, and 73. However, HPV 53 and 73 were always associated to other high-risk genotypes. Human papillomavirus types 31, 51, 52, 56, and 59 were detected in 1 case each. CONCLUSIONS: Human papillomavirus prevalence and patterns of type-specific HPV positivity were comparable with other studies. Current HPV vaccines should protect against HPV genotypes responsible for 77.4% of ICC in Portugal.